Toward a Switchover of Locomotives in the Global Economy - Canuto, Otaviano (World Bank, Washington, DC, 2012)
The recovery in advanced economies is now exhibiting several signs of fragility and the medium-term growth prospects for these economies also look difficult. Could developing economies 'switch over' to become locomotives in the global economy, providing a countervailing force against downward trends? The view taken here says, yes, as long as appropriate domestic policies and reforms are pursued in developing countries.